Presentatie "Leiden tegen apartheid - Steun de BOA". Tweede van rechts: BOA-voorman Esau du Plessis - Stegeman, Jan, (1979)
Presentatie "Leiden tegen apartheid - Steun de BOA". Tweede van rechts: BOA-voorman Esau du Plessis.